The Effect of Using Some Teaching Methods on Learning the Skill of the Snatch Students - Ali Sadiq Shaker Al-Sahlawi1 , Noha Youssef Hashim Al-Amiri2 , Bashar Abbood Fadel1 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Included five chapters, as the first chapter contained the definition of research that includes learning the skillof The Snatch using modern teaching methods. The research problem has been identified, which consistsin not using these methods in teaching the skills of The Snatch and Clean and Jerk and various within theeducational curriculum scheduled and followed for students of the first stage In the College of PhysicalEducation and Sports Science and the goal of the research to:- Knowing the effect of the researched methods(inclusion, self-revision, and commanding) on learning the skill of The Snatch for students with weightlifting. Exposing the best methods (inclusion, self-revision) has an impact on learning the skill of The Snatchstudents. As for the second chapter, it contained theoretical studies that have a relationship with the teachingmethods that were used in the research, while the third chapter included the research methodology and itsfield procedures if the researchers used the experimental approach to its suitability the nature of the problemand the first experimental group used the method of self-review (self-examination) as for the experimentalgroup The second is the method of inclusion (containment).